Pengaruh Biomassa dan Waktu Fermentasi Mikroalga Alami dengan Penambahan Kotoran Sapi untuk Produksi Biogas - Dheo Irfandanny; Novirina Hendrasarie (Fakultas Teknik, 2023)
Biogas is one of the alternative energy sources that has become increasingly popular. Several studies have found that microalgae are effective in producing biogas. This research aims to explore the potential of natural microalgae as an alternative energy source for biogas production. The study was conducted by utilizing microalgae naturally present in bozzem water and drainage. The reactor used in this study is an Anaerobic stirred-tank reactor. The addition of cow manure is used as a supplementary substrate to enhance nutrient levels during the fermentation process. Various fermentation times and biomass concentrations were applied to determine the optimal reactor conditions for biogas production. Natural microalgae from the drainage and bozzem water have an impact on biogas production. The produced biogas was analyzed to determine CH4 (methane) and CO2 (carbon dioxide) concentrations. The best results in this study were obtained from drainage microalgae, which produced biogas with CH4 concentration of 50.17% and CO2 concentration of 40.14% at a biomass concentration of 40%. Meanwhile, bozzem microalgae produced biogas with CH4 concentration of 32.28% and CO2 concentration of 25.02% at a biomass concentration of 30%.